Children's Understanding and Experience of Anger Within Their Peer Groups - Hamel, Nicole J (2013)
The purpose of this study was to describe how children understand, experience and express their anger with others in their peer group, from their perspectives. Semi-structured focus groups were conducted with third grade students in an elementary school. Children were asked three questions: 1) What did you learn about dealing with anger this week? 2) What are some good/positive things that happened between you and your classmates this week? 3) What are some not so good or negative things that happened between you and your classmates this week? Six themes emerged from analysis of the transcripts of the semi-structured focus groups: Managing Anger, Roots of Anger, Expression of Anger, Consequences of Anger, Avoidance Strategies, and Impact of Anger on Relationships. Children think that anger is bad, and they view anger and aggression as the same. Implications for counseling and research are offered